Hell's bells - Connolly, John (Hodder London, 2011)
Samuel Johnson - with help from Boswell and a demon named Nurd - has sent the demons back to Hell. But Mrs Abernathy does not take defeat lying down. She reopens the portal and sucks Samuel and Boswell down into the underworld, with an ice-cream van full of dwarfs, and two policemen. Can this eccentric gang defeat the forces of Evil? And is there life after Hell for Nurd?